2005
DOI: 10.14411/eje.2005.034
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and niche separation of cocoon parasitoids in different forest types with endemic populations of their host, the Common Pine Sawfly Diprion pini (Hymenoptera: Diprionidae)

Abstract: Abstract. Species diversity and potential impact of cocoon parasitoids on the abundance of the common pine sawfly, Diprion pini L. (Hymenoptera: Diprionidae), were explored in different forest habitats, with endemic sawfly populations, by the regular exposure of laboratory reared sawfly cocoons. Different cocoon spinning sites of the sawfly were simulated by exposing cocoons at several strata (soil, litter, trunk and stem of pine trees) in a forest. In more fertile, mixed spruce/pine-forests, parasitism on exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Although the natural enemies hypothesis was originally motivated by observations from agricultural systems, observations of reduced forest pest damage in more diverse forest stands has advanced its consideration in forest systems (e.g. For other forest defoliators, such as the spruce budworm, Choristoneura fumiferana Clemens (Lepidoptera: Tortricidae), and autumnal moth, Epirrita autumnata Borkhausen (Lepidoptera: Geometridae), predation and parasitism, especially by generalists, are higher in more diverse forest stands (Cappuccino et al, 1998;Quayle et al, 2003;Riihimäki et al, 2005), although the response by specialist parasitoids may be opposite (Herz & Heitland, 2005). For other forest defoliators, such as the spruce budworm, Choristoneura fumiferana Clemens (Lepidoptera: Tortricidae), and autumnal moth, Epirrita autumnata Borkhausen (Lepidoptera: Geometridae), predation and parasitism, especially by generalists, are higher in more diverse forest stands (Cappuccino et al, 1998;Quayle et al, 2003;Riihimäki et al, 2005), although the response by specialist parasitoids may be opposite (Herz & Heitland, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the natural enemies hypothesis was originally motivated by observations from agricultural systems, observations of reduced forest pest damage in more diverse forest stands has advanced its consideration in forest systems (e.g. For other forest defoliators, such as the spruce budworm, Choristoneura fumiferana Clemens (Lepidoptera: Tortricidae), and autumnal moth, Epirrita autumnata Borkhausen (Lepidoptera: Geometridae), predation and parasitism, especially by generalists, are higher in more diverse forest stands (Cappuccino et al, 1998;Quayle et al, 2003;Riihimäki et al, 2005), although the response by specialist parasitoids may be opposite (Herz & Heitland, 2005). For other forest defoliators, such as the spruce budworm, Choristoneura fumiferana Clemens (Lepidoptera: Tortricidae), and autumnal moth, Epirrita autumnata Borkhausen (Lepidoptera: Geometridae), predation and parasitism, especially by generalists, are higher in more diverse forest stands (Cappuccino et al, 1998;Quayle et al, 2003;Riihimäki et al, 2005), although the response by specialist parasitoids may be opposite (Herz & Heitland, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Jactel et al, 2005;Koricheva et al, 2006;Jactel & Brockerhoff, 2007). For other forest defoliators, such as the spruce budworm, Choristoneura fumiferana Clemens (Lepidoptera: Tortricidae), and autumnal moth, Epirrita autumnata Borkhausen (Lepidoptera: Geometridae), predation and parasitism, especially by generalists, are higher in more diverse forest stands (Cappuccino et al, 1998;Quayle et al, 2003;Riihimäki et al, 2005), although the response by specialist parasitoids may be opposite (Herz & Heitland, 2005). Forest stand diversity may therefore alter the interactions between FTC and its natural enemies, with potential implications for the dynamics of FTC populations in the mixedwood boreal forest.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Scots pine (Pinus sylvestris L.) needle N contents increase with soil N contents (Björkman et al 1991, Raitio 1999, which have also been shown to affect the contents of secondary defense compounds (Björkman et al 1991, Kainulainen et al 1996. In addition, predators and parasitoids of defoliators have been shown to be affected by site fertility (Hanski & Parviainen 1985, Herz & Heitland 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Our study was focused on: (i) collecting data about distribution, abundance and detectability of chafer beetles within the study area, also in the light of the used sampling method (airtraps), and (ii) on investigating ecological factors associated to spatial niche partitioning between the two species. Spatial niche partitioning was explored in several studies on insects (Wassmer, ; Herz and Heitland, ; Friberg et al ., ,b; Gilbert et al ., ), and in some cases has been considered as a key evolutionary phenomenon responsible for adaptive speciation (Friberg et al ., ).…”
Section: Introductionmentioning
confidence: 99%